Conservation of Rafflesia hasseltii Suringar in Bukit Tiga Puluh National Park, Riau-Jambi - Ervizal A.M Zuhud; Nina Hernindiah; Agus Hikmat (Department of Forest Resources Conservation and Ecotourism - IPB University, 1999)
Ru/flesrcr ltasselfrr Suringar was fourid at Bukit Tiga Pululi National Park. Local name of this species is